Constitutive p21-activated Kinase (PAK) Activation in Breast Cancer Cells as a Result of Mislocalization of PAK to Focal Adhesions - Stofega, Mary R. (The American Society for Cell Biology, 2004)
Cytoskeletal remodeling is critical for cell adhesion, spreading, and motility. p21-activated kinase (PAK), an effector molecule of the Rho GTPases Rac and Cdc42, has been implicated in cytoskeletal remodeling and cell motility. PAK kinase activity and subcellular distribution are tightly regulated by rapid and transient localized Rac and Cdc42 activation, and by interactions mediated by adapter proteins. Here, we show that endogenous PAK is constitutively activated in certain breast cancer cell lines and that this active PAK is mislocalized to atypical focal adhesions in the absence of high levels of activated Rho GTPases. PAK localization to focal adhesions in these cells is independent of PAK kinase activity, NCK binding, or GTPase binding, but requires the association of PAK with PIX. Disruption of the PAK–PIX interaction with competitive peptides displaces PAK from focal adhesions and results in a substantial reduction in PAK hyperactivity. Moreover, disruption of the PAK–PIX interaction is associated with a dramatic decrease of PIX and paxillin in focal adhesions, indicating that PAK localization to these structures via PIX is required for the maintenance of paxillin- and PIX-containing focal adhesions. Abnormal regulation of PAK localization and activity may contribute to the tumorigenic properties of certain breast cancer cells.